2017
DOI: 10.5194/acp-2017-850
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial distribution and occurrence probability of regional new particle formation events in eastern China

Abstract: <p><strong>Abstract.</strong> In this work, the spatial extent of new particle formation (NPF) events and the relative probability of observing particles originating from different spatial origins around three rural sites in eastern China were investigated with the NanoMap method, using particle number size distribution (PNSD) data and air mass back trajectories. The length of the datasets used were 7-year, 1.5-year and 3-year at rural sites Shangdianzi (SDZ) in North … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…These values are comparable to earlier observations in urban Beijing and another regional background station in the North China Plain (NCP) (Wang et al, 2013). Earlier observations in the NCP and the Yangtze River Delta also show higher formation rates at urban sites than corresponding background sites by roughly a factor of 2 due to lower anthropogenic emissions at background sites (Wang et al, 2013;Dai et al, 2017;Shen et al, 2018). The much lower J 7 observed at the MT station is very likely associated with the low H 2 SO 4 concentration at this station, as we discussed above.…”
Section: Particle Formation and Growth Rates At Both Stationssupporting
confidence: 87%
See 1 more Smart Citation
“…These values are comparable to earlier observations in urban Beijing and another regional background station in the North China Plain (NCP) (Wang et al, 2013). Earlier observations in the NCP and the Yangtze River Delta also show higher formation rates at urban sites than corresponding background sites by roughly a factor of 2 due to lower anthropogenic emissions at background sites (Wang et al, 2013;Dai et al, 2017;Shen et al, 2018). The much lower J 7 observed at the MT station is very likely associated with the low H 2 SO 4 concentration at this station, as we discussed above.…”
Section: Particle Formation and Growth Rates At Both Stationssupporting
confidence: 87%
“…Actually, the wind conditions on other NPF event days at the MT station during our observation had similar characteristics that the wind directions were similar between 850 hPa and 10 m above ground level, indicating air masses were well mixed during NPF events. Earlier observations also found that NPF events happened uniformly within the mixing layer at their observation stations and that particle number size distribution remains roughly constant within the mixing layer (Shen et al, 2018;Lampilahti et al, 2021).…”
Section: Effect Of Topographymentioning
confidence: 79%
“…Since no decrease are shown by both formation and growth rates during 2020‐LOCK, it can be concluded that the number concentration of >25 nm particle “seeds” produced by NPF events were at least not reduced, if not increased, during the lockdown. In addition, the occurrence of NPF events normally spread on large scale of over 100 km in the North China Plain (Shen et al., 2018), which can produce considerably high potential of >25 nm particle, regionally. In contrast, according to the discussion in 3.3, the PN Ait emitted by local fossil fuel combustion, which can serve as “seeds” in haze formation, showed clear downtrend due to the lockdown.…”
Section: Resultsmentioning
confidence: 99%
“…The growth stagnation and the disappearance of the particle mode from our observations suggest that the spatial extent of NPF is limited to nearby areas in the north-west direction. 52,65 Therefore, a possible explanation for these observations could be that practically no NPF occurs in the clean air masses descending from the mountainous area until they are mixed with precursor vapors emitted in the North China Plain.…”
Section: New Particle Formation and The Evolution Of Particle Number ...mentioning
confidence: 99%